A case of its own? A review of Italy's colonisation of Eritrea, 1890-1941 - Morten Jerven; Donatella Strangio; Jacon Weisdorf (African Economic History Network (AEHN), 2021)
This paper considers Italy's short but intense colonisation of Eritrea in light of the more well-known European colonial histories in Africa. We review the Italian historiography on Italy's involvement in Eritrea, supplementing it with novel archival data. The focus is on the activities of private enterprises and agricultural settlements, and on the Italian state's colonial spending, particularly during Fascism. We reflect on the actual effects of these factors on Eritrea's development, as against those predicted by the leading theories, and show how these highlight the somewhat atypical nature of the case of Eritrea.
Keywords: 330; Kolonialismus; Italienisch; Wirtschaftsgeschichte; Eritrea; Italien